The Sprawling Planet: Simplifying the Measurement of Global Urbanization Trends - Gerten, Christian; Fina, Stefan; Rusche, Karsten (Frontiers in Environmental Science, 2019)
Recent decades have been characterized by a rapid and steady urbanization of the global population. This trend is projected to remain stable in the future and to affect land use patterns in multiple ways. Monitoring and measurement concepts for urbanization processes have presented difficulties with the multitude of driving forces and variations in urban form as well as the assessment of outcomes of sometimes contradictory objectives for economic, social, and environmental policies. The monitoring frameworks that are employed with the aim of assessing the land use changes related to urbanization break down this complexity into singular dimensions that can be measured with individual indicators. Such monitoring allows planners and policy analysts to assess new urban growth against sustainable development criteria. Examples include compact city policies that allow urbanization to happen in suitable locations rather than laisser-faire urbanization that can happen regardless of environmental impacts and resource efficiency. In this context, we note that monitoring methods are most often designed for case studies in Europe or North America where urban structures are rather mature and consolidated. However, such monitoring can provide crucial information on urban development at a phase at which structures are currently evolving and can potentially still be modified. This is frequently the case in developing countries. Given this background, this paper presents an approach to simplifying the measurement of the land use changes related to urbanization with a new methodology. This paper condenses the needed measurement components into two dimensions: land use inefficiency and dispersion. The method can be used globally based on the newly available Global Human Settlement (GHS) layer that is available from the European Commission at no cost. In an initial application of the method to over 600 cities worldwide, we show the land use trends related to urbanization by continent and city size. In summary, we observe a consolidation of urban centers worldwide and continued sprawl on the outskirts. In European cities, a consolidation phase of urban structures began earlier, and cities are more mature and develop less dynamically compared to those in other regions of the world. More in-depth analyses of case studies present results for Paris, France, and Chicago, United States. In the case of Paris, the method helps to illustrate the growth pressures that led to massive urban sprawl on the outskirts with a continued densification of the inner city. In the case of Chicago, we observe a type of urban sprawl that goes along with the waves of suburbanization with population loss in the inner city and continued urban sprawl on the outskirts that are consolidated over time.